DIFFERNCES BETWEEN ULTRASONOGRAPHY AND OTHER RADIOLOGICAL INSTRUMENTS - Fayzullayeva M.B; Sayfiddin Hoji Qadriddin (TADQIQOTLAR, 2025)
Summary: Annotation.  Recent  guidelines  recommend  the  prioritized  use  of ultrasonography as the main imaging method for women under the age of 45, with mammography being considered when additional imaging is deemed necessary.